Fracturing fluid breaker carrier and preparation method and application thereof
The fracture liquid breaking agent carrier prepared by the disc particle maker and the holes method solves the problem of poor temperature resistance and high preparation cost of existing carrier, realizes the effect of extending the time of collagen and reducing costs. It is suitable for industrialized production. Essence
Patent Information
- Application Number
- CN202410833584.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-06-26
AI Technical Summary
The existing fracturing liquid grinding agent carrier materials have poor temperature resistance, complex preparation process and high cost, making it difficult to achieve industrial mass production.
A combination of a coefficient of a disc particlers, through mixed pores, lime, alpine, silicon sand, and alkaline stimulus solution to form a microsphere carrier, and to form a hollow or porous structure through high temperature burning sex.
The time of the fracture liquid is extended, it significantly improves the delayed glue ability of the fissure, reduces the cost of equipment, and is suitable for industrial production.
Smart Images

Figure CN118562480B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fracturing fluid breaker, and in particular relates to a fracturing fluid breaker carrier and a preparation method and application thereof. Background Art
[0002] The capsule-ball breaker is composed of a capsule-coated carrier and a capsule-core breaker. The role of the capsule-coated carrier is to prevent the breaker from contacting the fracturing fluid during fracturing, causing it to break and hydrate prematurely, thereby losing its ability to create fractures and carry sand. After the fracturing construction is completed, the capsule-coated carrier is squeezed and broken by the stress of fracture closure, and the capsule-core breaker is released to reduce the viscosity of the high-viscosity fracturing fluid and hydrate it (if it is not hydrated and broken, the high-viscosity fracturing fluid will be difficult to return to the formation smoothly, and it is easy to block the fractures and affect the outflow of oil and gas), so that it can be returned and discharged smoothly. Therefore, the breaker carrier can delay the breaking time of the frozen fracturing fluid, maintain the high viscosity of the fracturing fluid to ensure its ability to create fractures and carry sand during fracturing.
[0003] At present, most of the breaker carrier materials are thermoplastic polymer capsule carriers, which often have poor temperature resistance and are prone to creep damage when the temperature is high, resulting in a too short delay in breaking the gel. In addition, the carrying method of this polymer capsule carrier (Wurster fluidized bed method, i.e. fluidized solidification method: suspending the breaker particles in a flowing hot air flow while spraying atomized polymer solution and solidifying to form a capsule) is not only easily affected by factors such as the hot air flow rate, but also has high equipment costs, which is not conducive to industrial mass production. In addition, paraffin and ceramic materials are also commonly used breaker carrier materials, among which paraffin has poor temperature resistance and melts too quickly, and ceramic carriers have good compressive strength, but their preparation process is complicated and costly.
[0004] Scholars have invented an oil phase suspension dispersion solidification method to prepare degumming agent carriers: the raw materials are added with water to form a slurry, and then added to the high-speed rotating oil phase to obtain the carrier. However, this method requires a large amount of oil phase, which not only increases the preparation cost, but also makes it extremely difficult to clean the residual oil phase on the surface of the carrier afterwards. In addition, this method also has problems such as low production capacity, difficulty in industrialization, and poor control of carrier pores. Summary of the invention
[0005] In view of the problems in the prior art, the present invention provides a fracturing fluid breaker carrier and a preparation method and application thereof.
[0006] The fracturing fluid breaker carrier comprises, by weight, 25 to 30 parts of porogen, 4 to 10 parts of quicklime, 36 to 40 parts of metakaolin, 12 to 16 parts of silica sand, and 15 to 20 parts of alkaline activator solution.
[0007] The alkaline activator is a Na2CO3 solution with a mass fraction of 6-12%.
[0008] The porogen is anhydrous calcium chloride with a particle size of 30-50 meshes. Its deliquescent property makes it very easy to adhere to metakaolin when wet, and compared with the conventional porogen NaCl, its solubility is higher and it is easier to wash away afterwards, so that the microspheres form a porous or cavity structure. The present invention can adjust the void ratio of the carrier by changing the amount of the porogen CaCl2 added in the dry material and its particle size.
[0009] The silica sand is 1250 mesh ultrafine silica sand, which is used to improve the silicon-aluminum ratio of metakaolin and enhance the curing strength.
[0010] The preparation method of the fracturing fluid breaker carrier is as follows: the raw materials are mixed and granulated by a disc granulator to obtain microspheres; the microspheres are then soaked to form pores and calcined to obtain the fracturing fluid breaker carrier.
[0011] The specific process of disc granulator granulation is: porogen, quicklime, kaolin and silica sand are mixed evenly in proportion in the granulator, and then atomized alkali activator solution is intermittently and evenly sprayed into the granulator to obtain microspheres; usually when spraying the alkali activator solution, a pneumatic spray bottle is used to spray the alkali activator solution intermittently into the granulator that is continuously rotating at a uniform speed. The pneumatic spray bottle needs to be fully inflated and pressurized, and the alkali activator solution is atomized into tiny droplets and sprayed evenly, which avoids uneven wetting of the kaolin and is beneficial to granulation.
[0012] In the present invention, when the alkaline activator solution is sprayed, calcium oxide will also react with water to generate calcium hydroxide (strong base), which works together with the alkaline activator solution to activate the metakaolin reaction to form a three-dimensional network structure gel with stable and durable properties.
[0013] Since scattered metakaolin always preferentially adheres to the microspheres that have been initially spherical, if there are high requirements for the sphericity of the prepared microspheres, the porogen, quicklime, part of the metakaolin and silica sand can be mixed evenly in a granulator according to proportion and sprayed with atomized alkaline activator solution. At this time, the amount of metakaolin is 33% to 50% of the total amount of metakaolin. When the microsphere embryo is observed to be initially formed in the disc, the remaining metakaolin is added to the disc in batches and sprayed with atomized alkaline activator solution. Generally, the remaining metakaolin is added in 3 to 4 batches, and the atomized alkaline activator solution is sprayed once for each batch of metakaolin added. In this way, the particle size of the microspheres can be adjusted while improving the sphericity.
[0014] When the initial formation of microsphere embryos is observed in the disc, the remaining metakaolin is added to the disc in batches and sprayed with atomized alkaline activator solution. Generally, the remaining metakaolin is added in 3 to 4 batches, and the atomized alkaline activator solution is sprayed once each time a batch of metakaolin is added. This can adjust the particle size of the microspheres while improving the sphericity.
[0015] The prepared microspheres are dried, excess dry powder is sieved out, soaked in water to make pores, filtered, rinsed, and calcined to obtain a fracturing fluid breaker carrier.
[0016] The rotation speed of the disc granulator is set to 50-70 r / min, and the inclination angle of the disc granulator turntable is set to 45-60 degrees.
[0017] When soaking to form pores, the mass ratio of microspheres to water is 1.5:1~2:1, and the soaking time is 40~60min.
[0018] The calcination temperature is 800-1000° C., and the calcination time is 5-10 hours.
[0019] The fracturing fluid breaker carrier of the present invention can be used in the controlled release of fracturing fluid breaker. The breaker is carried in the prepared breaker carrier in the form of solution absorption, evaporation and crystallization, and then wrapped and packaged with resin to obtain a slow-release fracturing fluid breaker for delaying the fracturing time of the fracturing fluid.
[0020] The present invention has the following effects:
[0021] (1) The deliquescent nature of CaCl2 in the present invention makes it very easy to adhere to kaolin when it gets wet. Under the action of the disc granulator, the porogen CaCl2 is wrapped by the kaolin to form a core-shell carrier structure. The Na2CO3 solution and the quicklime after contact with water are both alkaline. The two work together to activate the "shell" (kaolin) to form a three-dimensional network structure gel, i.e., microspheres, which are stable and durable.
[0022] (2) After the microspheres are naturally dried and the excess dry powder is sieved out, they are soaked in tap water, filtered, and then rinsed with tap water to dissolve and completely rinse the "core" porogen CaCl2, forming a hollow or porous bearing space. After high-temperature calcination at 800-1000°C, the microspheres have good compressive strength and corrosion resistance. In deep high-temperature environments, creep damage will not occur, resulting in premature release of the breaker, which can extend the time for delayed breaker breaking, significantly improving the ability of the fracturing fluid to delay breaker breaking.
[0023] (3) The present invention avoids the complicated preparation process of the Wurster fluidized bed solidification method by combining the disc granulation process with the pore-forming method, thereby eliminating the high cost of fluidized bed equipment.
[0024] (4) Compared with the existing oil phase suspension dispersion solidification method, the present invention has a simpler preparation process, eliminates the additional cost of the oil phase, greatly improves the single preparation output, and is more suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The method for preparing a fracturing fluid breaker carrier according to the present invention can be more easily understood by combining the following figures and the description of the embodiments, wherein:
[0026] Figure 1 This is a schematic diagram of the preparation method of the fracturing fluid breaker carrier of the present invention;
[0027] Figure 2 A fracturing fluid breaker carrier prepared according to the method of the present invention;
[0028] Figure 3 It is the internal bearing space exposed by the partial crushing of microspheres after the stress extrusion and crushing of the fracturing fluid breaker carrier;
[0029] Figure 4 The fracturing fluid breaker carrier obtained in Example 1;
[0030] Figure 5 The fracturing fluid breaker carrier obtained in Example 3;
[0031] Figure 6 In the example, the fracturing fluid breaker carrier carries two breakers (AH and APS) and the existing capsule breaker in a rheometer (temperature 90°C, shear rate 170s -1 ) Comparison of delayed gel breaking effect. DETAILED DESCRIPTION
[0032] Example 1
[0033] A fracturing fluid breaker carrier, whose raw materials are composed of: anhydrous CaCl2 400g, quicklime CaO 75g, metakaolin 600g, silica sand 240g, and alkaline activator solution 300g, in parts by weight;
[0034] The alkaline activator solution is a Na2CO3 solution with a mass fraction of 10%;
[0035] The anhydrous CaCl2 particle size is 30-40 mesh;
[0036] The silica sand is 1250 mesh ultra-fine silica sand;
[0037] The specific preparation process is:
[0038] (1) Prepare 10% Na2CO3 solution as an alkaline activator, then transfer the solution into a pressure spray bottle and fully inflate and pressurize it;
[0039] (2) Pour kaolin, quicklime, ultrafine silica sand and anhydrous CaCl2 into the turntable of the disc granulator, set the speed to 60r / min, rotate for 1min and mix evenly; then use a pneumatic spray bottle to intermittently and evenly spray the atomized alkaline activator solution into the turntable, during which the disc granulator continues to rotate at a speed of 60r / min, and observe the state of the granulator turntable at all times. When a large area of spheroidization is observed in the turntable, stop spraying, and then keep the disc granulator rotating for 5min, then reduce the speed of the disc granulator to 0, turn off the power of the granulator, and take out the preliminarily prepared microspheres in the turntable;
[0040] (3) Spread the microspheres flat and air dry, sieve out excess dry powder and a small amount of spheres with abnormally large particle sizes, and then soak them in tap water for 50 minutes (to fully dissolve the coated CaCl2), filter them with a 50-mesh sieve, and rinse off the CaCl2 remaining on the surface of the microspheres. Dry them again, and then place them in a muffle furnace and calcine them at 850°C for 6 hours to increase the strength, thereby obtaining a hollow fracturing fluid breaker carrier.
[0041] The obtained breaker carrier has a particle size of 350μm~430μm and an average wall thickness of about 30μm, which meets the particle size standard (425μm~850μm) for capsule breaker products for fracturing specified in Q / 0111CAL 010-2017.
[0042] Example 2
[0043] A fracturing fluid breaker carrier, whose raw materials are composed of: anhydrous CaCl2 575g, quicklime CaO 75g, metakaolin 830g, silica sand 320g, and alkaline activator solution 350g, in parts by weight;
[0044] The alkaline activator solution is a Na2CO3 solution with a mass fraction of 12%;
[0045] The anhydrous CaCl2 particle size is 40-50 mesh;
[0046] The silica sand is 1250 mesh ultra-fine silica sand;
[0047] The specific preparation process is:
[0048] (1) Prepare 12% Na2CO3 solution as an alkaline activator, then transfer the solution into a pressure spray bottle and fully inflate and pressurize it;
[0049] (2) Pour kaolin, quicklime, ultrafine silica sand and anhydrous CaCl2 into the turntable of the disc granulator, set the speed to 60r / min, rotate for 1min and mix evenly; then use a pneumatic spray bottle to intermittently and evenly spray the atomized alkaline activator solution into the turntable, during which the disc granulator continues to rotate at a speed of 60r / min, and observe the state of the granulator turntable at all times. When a large area of spheroidization is observed in the turntable, stop spraying, and then keep the disc granulator rotating for 5min, then reduce the speed of the disc granulator to 0, turn off the power of the granulator, and take out the preliminarily prepared microspheres in the turntable;
[0050] (3) Spread the microspheres flat and air dry, sieve out excess dry powder and a small amount of spheres with abnormally large particle sizes, and then soak them in tap water for 60 minutes (to fully dissolve the coated CaCl2), rinse off the CaCl2 remaining on the surface of the microspheres, dry them again, and then place them in a muffle furnace and calcine at 850℃ for 6 hours to increase the strength, thereby obtaining a hollow fracturing fluid breaker carrier.
[0051] The obtained breaker carrier particle size is 450μm~580μm, and the average wall thickness is about 50μm, which meets the particle size standard (425μm~850μm) of capsule breaker products for fracturing specified in Q / 0111CAL 010-2017.
[0052] Example 3
[0053] A fracturing fluid breaker carrier, whose raw materials are composed of: anhydrous CaCl2 400g, quicklime CaO 75g, metakaolin 600g, silica sand 240g, and alkaline activator solution 300g, in parts by weight;
[0054] The alkaline activator solution is a Na2CO3 solution with a mass fraction of 10%;
[0055] The anhydrous CaCl2 particle size is 30-40 mesh;
[0056] The silica sand is 1250 mesh ultra-fine silica sand;
[0057] The specific preparation process is:
[0058] (1) Prepare 10% Na2CO3 solution as an alkaline activator, then transfer the solution into a pressure spray bottle and fully inflate and pressurize it;
[0059] (2) Pour 300g of metakaolin, quicklime, ultrafine silica sand and anhydrous CaCl2 into the turntable of the disc granulator, set the speed to 60r / min, rotate for 1min and mix evenly; then use a pneumatic spray bottle to intermittently and evenly spray the atomized alkaline activator solution into the turntable, during which the disc granulator continues to rotate at a speed of 60r / min, and observe the state of the granulator turntable at all times. When it is observed that the CaCl2 in the turntable is initially entrained into granules by the spheroidizing agent, briefly spray the atomized alkaline activator solution to wet it, then add 100g of metakaolin to the turntable, and briefly spray the atomized alkaline activator solution (during which the disc granulator continues to rotate at 60r / min), repeat the above steps of adding metakaolin and spraying liquid 3 times, then keep the disc granulator rotating for 5min, reduce the speed of the disc granulator to 0, turn off the power of the granulator, and take out the preliminarily prepared microspheres in the turntable;
[0060] (3) The steps here are the same as step (3) of Example 1, and the obtained breaker carrier (see Figure 5 ) compared with Example 1 (see Figure 4 ) was significantly improved, proving that the sphericity of the breaker carrier can be significantly improved by adding metakaolin in batches.
[0061] Experimental Example 1
[0062] The fracturing fluid breaker carrier prepared in Example 1 was used to carry two breakers AH and ammonium persulfate (APS) in the form of solution absorption, evaporation and crystallization, respectively, to prepare AH microspheres and APS microspheres. Since the solubility of AH breaker in water (20g / 100g water) is much lower than that of APS breaker (58g / 100g water), in order to prevent the excessive amount of ammonium persulfate breaker from being effectively carried by the carrier microspheres, the ratio of the carrier microspheres to the APS solution when absorbing and carrying APS is 1:1, and the mass ratio of the carrier microspheres to the AH solution when carrying AH is 1:2. Table 1 shows the corresponding ratios of the breaker and the carrier in the process of absorbing and carrying the breaker:
[0063] .
[0064] The uniformly prepared guar jelly fracturing fluid was used to test the sustained-release breaking effect of AH microspheres and APS microspheres: 42 ml of guar jelly fracturing fluid was measured with a measuring cylinder and poured into the sample tube of the rheometer, and 0.643 g of AH breaking microspheres (corresponding to 0.1 g of AH) were added, and the rheometer operation program was set (temperature increased to 90 °C, shear rate increased to 170 s -1 ), record the viscosity change. When testing APS microspheres, 0.643g AH breaking microspheres were replaced with 0.583g APS breaking microspheres (corresponding to 0.1g APS), and the rest remained unchanged. 0.1g of AH breaking agent and 0.1g of APS breaking agent were used to perform the above breaking experiment for comparison. The breaking curve is shown in Figure 4 .
[0065] from Figure 4 From the breaking curves of AH, APS, AH breaking microspheres, and APS breaking microspheres, both AH breaking microspheres and APS breaking microspheres have the effect of delayed breaking, but the frozen gel fracturing fluid of the AH breaking microsphere group still maintains a relatively high viscosity in the end, which means that part of the AH carried may react with the carrier microspheres and be consumed, resulting in the failure to break the frozen gel fracturing fluid in the end. Therefore, the breaker carrier of the present invention is suitable for carrying ammonium persulfate breaker. In view of this, the APS breaker microspheres in Experimental Example 1 were encapsulated with resin, and then the encapsulated APS breaking microspheres and BSA-406 capsule breaker containing 0.1g of APS were used to carry out the breaking experiment in Experimental Example 1. The corresponding viscosity decrease curve of the frozen gel fracturing fluid is shown in FIG. Figure 6 It can be seen that the delayed breaking ability of the encapsulated APS breaker microspheres is better than that of the BSA capsule breaker, which proves that the fracturing fluid breaker carrier of the present invention is feasible.
Claims
1. A fracturing fluid breaker carrier, characterized in that: The raw material composition is as follows: 80 parts of porogen, 15 parts of quicklime, 120 parts of metakaolin, 48 parts of silica sand, and 60 parts of alkaline activator solution by weight; the alkaline activator solution is a Na2CO3 solution with a mass fraction of 10%; the porogen is anhydrous calcium chloride, and the particle size of the porogen is 30 to 50 meshes; the silica sand is ultrafine silica sand with a mesh size of 1250; The preparation method is as follows: the raw materials are mixed and then granulated by a disc granulator to obtain microspheres; the microspheres are then soaked to form pores and calcined to obtain a fracturing fluid breaker carrier; The specific process of the disc granulator granulation is: the porogen, quicklime, metakaolin and silica sand are mixed evenly in the granulator according to the proportion, and then the atomized alkaline activator solution is sprayed into the granulator intermittently and evenly to obtain microspheres; When soaking to form pores, the mass ratio of microspheres to water is 1.5:1~2:1, and the soaking time is 40~60min; The calcination temperature is 800~1000℃, and the calcination time is 5~10h.
2. A fracturing fluid breaker carrier according to claim 1, characterized in that: The specific process of granulation by the disc granulator is as follows: the porogen, quicklime, part of kaolin and silica sand are mixed evenly in proportion in the disc granulator and sprayed with atomized alkali activator solution. When the microsphere embryo is initially formed in the disc, the remaining kaolin is added to the disc in 3-4 batches. Each time a batch of kaolin is added, the atomized alkali activator solution is sprayed once to obtain microspheres.
3. A fracturing fluid breaker carrier according to claim 1, characterized in that: The rotation speed of the disc granulator is set to 50-70 r / min, and the inclination angle of the disc granulator turntable is set to 45-60 degrees.
4. Use of the fracturing fluid breaker carrier according to claim 1 in breaker controlled release.
Citation Information
Patent Citations
Method for preparing alkali-activated gel material by use of low-temperature calcined intercalated kaolin
CN103613296A
Preparation method and application of porous geological polymer microspheres
CN107973559A